Mathematics and the physical world - Kliene Morris (New York Dover, 1981)
Stimulating account of development of basic mathematics from arithmetic, algebra, geometry and trigonometry, to calculus, differential equations and non-Euclidean geometries. Also describes how math is used in optics, astronomy, motion under the law of g
Keywords: Mathematics